Mose als Ägypter?: Die letzten Seiten der Schaffhauser »Ältesten Urkunde« - Arnold, Günter (Zeitschrift für Theologie und Kirche, 2018)
Johann Gottfried Herder's »Älteste Urkunde des Menschengechlechts« (1774-1776) monitors comparative religious perspectives on his interpretation of Gen 1-11. The oldest manuscript version was drafted 250 years ago and rediscovered in 1980, before the bulk of the text was edited 25 years ago. Transcribed here for the first time is an addition to the manuscript, in which Herder seeks to determine the relationship between Egyptian culture and Mosaic history.